2006
DOI: 10.1007/s00253-006-0387-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prokaryotic collagen-like sequences derived from streptococcal Scl1 and Scl2 proteins as a source of recombinant GXY polymers

Abstract: Collagen triple helix, composed of the repeating Gly-Xaa-Yaa (GXY) sequence, is a structural element found in all multicellular animals and also in some prokaryotes. Long GXY polymers are highly regarded components used in food, cosmetic, biomedical, and pharmaceutical industries. In this study, we explore a new concept for the production of recombinant GXY polymers which are based on the sequence of "prokaryotic collagens", the streptococcal collagen-like proteins Scl1 and Scl2. Analysis of 50 Scl variants id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 35 publications
3
108
0
Order By: Relevance
“…While some triplets identified in human collagens that are part of the integrin binding sites, such as GFO, GMO, and GEN, are never found within the Scl-CL regions, other triplets may occur frequently, including GER (3.20%), GEK (7.08%), and GLP (4.89%) (18). Interestingly, the RGD cryptic motif is common in the Scl2-CL regions 3 and is also found in recently reported SclZ protein (38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some triplets identified in human collagens that are part of the integrin binding sites, such as GFO, GMO, and GEN, are never found within the Scl-CL regions, other triplets may occur frequently, including GER (3.20%), GEK (7.08%), and GLP (4.89%) (18). Interestingly, the RGD cryptic motif is common in the Scl2-CL regions 3 and is also found in recently reported SclZ protein (38).…”
Section: Discussionmentioning
confidence: 99%
“…2). Our earlier EM studies revealed that rScls share a common "lollipop-like" two-domain organization composed of the globular head formed by the V region and the lollipop stalk made by the fibrous CL region (17,18). Binding events between the r␣ 2 I domain and the CL region of P222 were observed in electron micrographs, and the location of bound r␣ 2 I appeared to be the same in each case.…”
Section: Glpger Sequence In Rscl Is Sufficient For Integrin Binding-mentioning
confidence: 98%
See 2 more Smart Citations
“…30 The identification of this new group of collagens provides potential for development of new, recombinant biomedical materials. 31 Several have now been studied after expression in E. coli. 28 They do not contain any hydroxyproline, and even though some native bacterial structures are glycosylated, this is not the case with the recombinant products.…”
Section: Recombinant Bacterial Collagen: An Emerging Systemmentioning
confidence: 99%